In Search of Excellence: CSR Initiatives by Indian Companies - Dasari, Shailendra (Prabandhan: Indian Journal of Management, 2012)
Corporate social responsibility has been embedded in the ethos of Indian companies for more than a century . Mahatma Gandhi wanted the business houses to be the custodians of the society. While acts of philanthropy have been a regular feature of the corporate houses discharging their social responsibility, the significance of CSR in its modern form is yet to be realized by the vast majority of Indian companies. This paper is an attempt to emphasize the need for Indian companies to embrace CSR; take a stock of the commitment of Indian companies to CSR imperative; highlight the best practices followed by select Indian companies on the CSR front and the need for others to follow suit for their survival and growth. Apart from carrying out literature survey to understand the relevance and significance of CSR and the extent it is being practiced by Indian companies, empirical observations and information furnished in the annual reports of companies like Tata Steel, Microsoft India, Hindustan Petroleum and Orchid Chemicals & Pharmaceuticals has been made use of to further the objectives of this paper. Discussion of the findings and areas for further research have also been included in the present paper.